Investigation of In Vivo skin stiffness anisotropy in breast cancer related lymphoedema. Issue 1 (4th January 2016) - Coutts, L.V.; Miller, N.R.; Mortimer, P.S.; Bamber, J.C.
Abstract: There is a limited range of suitable measurement techniques for detecting and assessing breast cancer related lymphoedema (BCRL). This study investigated the suitability of using skin stiffness measurements, with a particular focus on the variation in stiffness with measurement direction (known as anisotropy). In addition to comparing affected tissue with the unaffected tissue on the corresponding site on the opposite limb, volunteers without BCRL were tested to establish the normal variability in stiffness anisotropy between these two corresponding regions of skin on each opposite limb. Multi-directional stiffness was measured with an Extensometer, within the higher stiffness region that skin typically displays at high applied strains, using a previously established protocol developed by the authors. Healthy volunteers showed no significant difference in anisotropy between regions of skin on opposite limbs (mean decrease of 4.7 +/−2.5% between non-dominant and dominant arms), whereas BCRL sufferers showed a significant difference between limbs (mean decrease of 51.0+/−16.3% between unaffected and affected arms). A large difference in anisotropy was apparent even for those with recent onset of the condition, indicating that the technique may have potential to be useful for early detection. This difference also appeared to increase with duration since onset. Therefore, measurement of stiffness anisotropy has potential value for the clinical assessment and diagnosis of skin conditions such as BCRL. The promising results justify a larger study with a larger number of participants.